Pengaruh Artificial Intelligence terhadap Perkembangan Kreativitas Peserta Didik dalam Pembelajaran Berbasis Deep Learning - Chintya Eria Suryawati; Adilla Putri Febriani; Salsabila Intan Iswidiarmi Suhadi; Sifana Aradesita; Vivi Rulviana (Universitas PGRI Madiun, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed education, particularly in supporting the implementation of Deep Learning-based instruction. Students' creativity, as one of the essential twenty-first-century competencies, needs to be continuously developed to generate innovative ideas and effective solutions to learning problems. This study aims to analyze the influence of Artificial Intelligence on students' creativity development in Deep Learning-based learning. The study employed a qualitative descriptive approach using the library research method. The data were analyzed using content analysis,. The results indicate that AI enhances students' creativity by providing adaptive, personalized, interactive, and problem-oriented learning experiences. Furthermore, AI supports the characteristics of Deep Learning by promoting conceptual understanding, critical thinking, collaboration, reflection, and meaningful learning. Therefore, the integration of AI can serve as an effective educational innovation to foster students' creativity when supported by teachers' competencies, digital literacy, and adequate technological infrastructure.